HUBUNGAN KEMANDIRIAN BELAJAR DAN MINAT BELAJAR SISWA DENGAN HASIL BELAJAR PRAKARYA SISWA KELAS VIII SMP MARDI LESTARI MEDAN - Surniaty Chalid; Hesty Rebecca Simorangkir (Universitas Negeri Medan, 2015)
ABSTRACT This study aims to 1 ) To determine the level of independence tendency of students in class craft subjects SMP Mardi Lestari Medan , 2 ) To determine the level of student interest in the tendency of subjects craft class VIII SMP Mardi Lestari Medan , 3 ) To determine the level of trend results student learning in subjects craft eighth grade students of SMP Mardi Lestari Medan , 4 ) to determine whether there is a relationship independent learning and students' interest in learning outcomes craft eighth grade students of SMP Mardi Lestari Medan. The population was eighth grade students of SMP Mardi Lestari field as many as 36 people . Sampling was carried out with total sampling technique . This data is captured by using a questionnaire to Independence Learning ( X1 ) and Student Interests ( X2) ; for Student Results In Subject craft ( Y ) captured using observation sheets , ie by observing the learning outcomes in making a picture frame of waste corn husk. To calculate the validity research instrument in the test with the product moment formula for the questionnaire , the acceptance rate at 5 % significance level. The test result obtained 40 independent learning questionnaire valid point , 10-point invalid while the reliability ( reliability ) of this research instrument was tested by using the formula alpha coefficient is equal to 0.78 categorized as high and the pilot questionnaire student interest obtained 40 valid items , 10 items invalid , while the reliability ( reliability ) of this research instrument was tested by using the formula alpha coefficient is equal to 1 categorized as very high. Based on the results obtained from the analysis of the data after testing with a number of respondents 36 people , it is generally found that the rate tends to be high where the Independence Learning Mi < Mh (100 < 119,44) and Level of Interest in Learning Students tend to be high where Mi < Mh (100 < 119,36), and Level Student Results In Subject craft tend to be high where Mi < Mh (162,5 < 194,28). From data analysis using product moment formula ryx1x2 = 0,65 compared with rtable = 0,329, of the value can be seen that rx12y > rtable which showed a strong relationship . While the hypothesis test obtained Fcount = 27,4 dan Ftable = 3,28, then Fcount > Ftable. This means that the hypothesis of relationship independent learning and student interest together with the results of class VIII student in the subject field craft SMP Mardi Lestari acceptable. Kata Kunci : Kemandirian belajar, minat belajar, hasil belajar.